1999
DOI: 10.1002/(sici)1099-0496(199908)28:2<109::aid-ppul6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage fluid cellularity and soluble intercellular adhesion molecule-1 in children with colds

Abstract: Viral colds are an important cause of respiratory symptoms in normal children. Studies in adults suggest that inflammation in the lower respiratory tract is associated with viral colds, but there are no data regarding inflammation and viral infection in the lower airway of normal children with colds. We, therefore, studied the lower airway of two groups of children: Group I, those with active coryzal symptoms and a respiratory virus isolated from bronchoalveolar lavage fluid (BALF); and Group II: asymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…First, trivial symptoms associated with the common cold may be associated with a similar pattern of neutrophil activation. In a very small group of children with rhinovirus colds, we have previously reported the presence of BAL fluid neutrophilia, 17 which may indicate that some neutrophil transmigration may occur during most trivial colds. We speculate that children with PVW have a propensity to recruit more neutrophils in their airways, and that neutrophil products trigger bronchoconstriction via activating other inflammatory cells, such as mast cells.…”
Section: Discussionmentioning
confidence: 95%
“…First, trivial symptoms associated with the common cold may be associated with a similar pattern of neutrophil activation. In a very small group of children with rhinovirus colds, we have previously reported the presence of BAL fluid neutrophilia, 17 which may indicate that some neutrophil transmigration may occur during most trivial colds. We speculate that children with PVW have a propensity to recruit more neutrophils in their airways, and that neutrophil products trigger bronchoconstriction via activating other inflammatory cells, such as mast cells.…”
Section: Discussionmentioning
confidence: 95%
“…This is particularly pertinent to influenza and RSV, as there were very few children in whom these viruses were detected. Secondly, we used neutrophilic lower airway inflammation as a surrogate marker for active pulmonary disease, as used by other authors [34,35]. We did not, however, test for additional indirect markers of viral infection such as Toll-like receptor 3 (TLR3), interferon gamma induced protein 10 (IP-10) or virus-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sICAM-1 in BAL has been described in adults with granulomatous lung diseases such as sarcoidosis, tuberculosis, hypersensitivity pneumonitis, and radiation pneumonitis (3,10,18) and in children exposed to second-hand smoke (16). Kasper et al (20) and Beck-Schimmer et al (5) have shown that a soluble form of ICAM-1 can be measured in the BAL of rats by Western blot analysis after immunoprecipitation and by ELISA, respectively.…”
Section: Discussionmentioning
confidence: 99%